2019
DOI: 10.3390/jcm8070932
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Denosumab and Alendronate on Cardiovascular and Renal Outcomes in Osteoporotic Patients

Abstract: A correlation between impaired bone metabolism, chronic kidney disease, and cardiovascular diseases (CVD) has been suggested. This study aimed to compare the effects of denosumab and alendronate, two anti-resorptive agents, on cardiovascular and renal outcomes in osteoporotic patients. Propensity score-matched cohort study comparing denosumab to alendronate users between January 2005 and December 2017 was conducted from a large medical organization in Taiwan. Risks of CVD development and renal function decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
(56 reference statements)
3
9
0
Order By: Relevance
“…As a higher rate of eGFR decline was observed in the denosumab group, this may translate to the possible worsening of CKD progression in denosumab users. This finding was consistent with a previous study comparing denosumab with alendronate, and the increase in renal function decline in the denosumab group was also observed in patients with poor baseline renal function with an eGFR of <60 mL/min/1.73 m 2 (aHR, 1.5; 95% CI 1.09-2.07; p = 0.0132) [18]. However, these results were in contrast to those of another FREEDOM extension study, which revealed no significant change in CKD stage between denosumab and placebo use [16].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As a higher rate of eGFR decline was observed in the denosumab group, this may translate to the possible worsening of CKD progression in denosumab users. This finding was consistent with a previous study comparing denosumab with alendronate, and the increase in renal function decline in the denosumab group was also observed in patients with poor baseline renal function with an eGFR of <60 mL/min/1.73 m 2 (aHR, 1.5; 95% CI 1.09-2.07; p = 0.0132) [18]. However, these results were in contrast to those of another FREEDOM extension study, which revealed no significant change in CKD stage between denosumab and placebo use [16].…”
Section: Discussionsupporting
confidence: 92%
“…Briefly, the CGRD contains individual patient-level EHR from the CGMH, providing 10–12% of health services reimbursed by Taiwan National Health Insurance (NHI) program in 2018 [ 19 ]. The data generalizability of CGRD has been validated in some disease populations [ 20 , 21 ], and the laboratory results have been used in kidney [ 18 , 22 , 23 ] and heart studies [ 24 ]. The CGRD data from January 2003 to December 2018 were used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcified area apparently diminished through 30 months of treatment and it was deemed necessary for ≥2 years for decalcification due to denosumab. Hsu et al [ 18 ] demonstrated that denosumab use is associated with a significant reduction in cardiovascular events compared to alendronate use with better adherence of >60% medication possession ratio. Despite no significant differences in MI and heart failure between the denosumab and raloxifene groups, our study did not obtain evidence of vascular calcification in X-ray or CT, owing to data limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab has been shown to exert protective effects against CVD [ 18 ]. Chen et al [ 19 ] reported that denosumab suppress the progression of coronary arterial calcification.…”
Section: Introductionmentioning
confidence: 99%